1998
DOI: 10.1021/np9705118
|View full text |Cite
|
Sign up to set email alerts
|

A Bioactive Secosterol with an Unusual A- and B-Ring Oxygenation Pattern Isolated from an Indonesian Soft Coral Lobophytum sp.

Abstract: A secosterol with a gorgosterol side chain and an unusual oxygenation pattern on the A and B rings was isolated from an Indonesian soft coral Lobophytum sp. The A and B rings of the reported compound 1 have hydroxyl groups at C-3 and C-7 and an epoxide ring at C-5-C-6. The structures of 1 was solved by 2D NMR methods and by chemical shift analogy to the known secogorgosterol 2. Compound 1 was found to have activity against human ovarian tumor and human leukemia cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 7 publications
3
39
0
Order By: Relevance
“…Since the first isolation of 9,11-secosterol from the gorgonian Pseudopterogorgia americana in 1972 [1], the members of this type of interesting sterol have increased very quickly and over scores of them have been discovered up to now, from a great variety of marine organisms involving acidians [2], sponges [3], gorgonians [4][5][6][7][8], and particularly soft corals [9][10][11][12][13][14][15][16][17]. Characterized by bond cleavage between C-9 and C-11, 9,11-secosterols have attracted much attention from chemists and pharmacologists due to their versatile biological effects such as antiviral, antimicrobial, cytotoxic, antiinflammatory activities [2,4,[7][8][9][10][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first isolation of 9,11-secosterol from the gorgonian Pseudopterogorgia americana in 1972 [1], the members of this type of interesting sterol have increased very quickly and over scores of them have been discovered up to now, from a great variety of marine organisms involving acidians [2], sponges [3], gorgonians [4][5][6][7][8], and particularly soft corals [9][10][11][12][13][14][15][16][17]. Characterized by bond cleavage between C-9 and C-11, 9,11-secosterols have attracted much attention from chemists and pharmacologists due to their versatile biological effects such as antiviral, antimicrobial, cytotoxic, antiinflammatory activities [2,4,[7][8][9][10][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, 13,14-secosteroids have been isolated from terrestrial plants (Bhandari et al 2006;Kirson et al 1976;Qiu et al 2008) and some of which have been demonstrated to possess anti-inflammatory activities (Qiu et al 2008). 9,11-Secosterols, the third group of secosteroids, are very rare in terrestrial organisms, and are instead of found primarily in marine invertebrates, mainly corals (Huang et al 2012;Cheng et al 2011;Chen et al 2011a, b;Ioannou et al 2009;Minh et al 2007;Epifanio et al 2007;Su et al 2006;Anta et al 2002;Aknin et al 1998;Morris et al 1998;He et al 1995;Lopp et al 1994;Koljak et al 1993;Ochi et al 1991;Fusetani et al 1989;Bonini et al 1983) and sponges (Van Altena et al 1999;De Rosa et al 1999;Rueda et al 1998;Lu and Faulkner 1997;Reddy et al 1997;Adinolfi et al 1994;Li et al 1994;Migliuolo et al 1992, Migliuolo et al 1991Capon and Faulkner 1985). In addition, 9,11-secosterols have been reported to display diverse bioactivities including cytotoxicity against cancer cell lines (Huang et al 2012;Cheng et al 2011;Chen et al 2011a, b;Su et al 2006;Morris et al 1998;Rueda et al 1998), anti-proliferative effects Inho Yang and Hyukjae Choi have contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies of the genus Lobophytum have led to the isolation of terpenoids, of which some have shown cytotoxic, [7][8][9][10] anti-HIV, 11) and antibacterial 12) activities. In this paper we report the isolation and structural elucidation of three new glycolipids 1-3 (Fig.…”
mentioning
confidence: 99%